Retrospective analysis of antipsychotic prescription models in correlation with symptoms of residual schizophrenia. Part 1. - Safonov, D. N.; Сафонов, Дмитро Миколайович (My University, 2020)
The therapeutic models of antipsychotic prescription in residual schizophrenia in highly dependent on various context factors, major – relevant treatment guidelines, local drug legal and registration status, local availability etc. and minor – psychiatrist personal experience, patients individual response and comorbid pathology profile etc. therefore it’s almost impossible to track down links between specific treatment model, possible NIDS manifestations or protective antipsychotic effects on negative symptoms in real clinical environment. Nevertheless finding the correlations between specific antipsychotic prescriptions and residual schizophrenia symptoms could highlight possible influence of some antipsychotics on specific symptoms in long term perspective. Aim – to evaluate correlations between antipsychotic prescription models and negative symptoms profile in patients with residual schizophrenia.
Keywords: residual schizophrenia; negative symptoms; therapeutic models; antipsychotics; antipsychotic course experience